Estimation of global solar radiation under clear sky radiation in Turkey - Togrul, IT; Togrul, H; Evin, D (Pergamon-Elsevier Science Ltd, 2000)
In this study, the usability of clear sky radiation for predicting the average global solar radiation was investigated. For this aim, the various regression analyses were applied by using (n) over bar/(N) over bar and (n) over bar/(N) over bar(nh) parameters. Also, equations which represent the two periods of the year, winter and summer, were developed by using these parameters. The equations developed by using (n) over bar/(N) over bar and (n) over bar/(N) over bar(nh) have approximately the same results. Having the better values of the equations developed by using the change of summer and winter is another result. In addition, the use of the RMSE and MBE in isolation is not an adequate indicator of model performance. Using the t-statistic method and the harmony of results obtained with each method will prove that the results are reliable (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: clear sky radiation; estimation of solar radiation; t-statistic